Simulation of Wideband Power Amplifier Design for Software Defined Radio (SDR) Using Feedback and Balanced Topology - Salleh, Azahari; Abd Aziz, M. Z. A; Mohamad, Najmiah Radiah; Hashim, Nik Mohd Zarifie; Ja'afar, Abd Shukur (2013)
This paper presents the design of power amplifier based on balanced and feedback topology for Software Defined Radio (SDR) using Agilent Advanced Design System (ADS) software. There is a growing interest in SDR in recent years upon the development of new technologies which that capable to support a coverage of Global System for Mobile (GSM), Third Generation (3G) and Wireless Local Area Network (WLAN) at the same location provided by one base station compare to before which is needed a separate base station for different channel bandwidth. The main objective of this research is to design a wideband power amplifier for SDR system that can support wide range frequency from 1.7 GHz to 2.7 GHz using GaAs Enhancementmode pHEMT transistor from Avago Technologies. The relevant amplifier theory with detailed descriptions of design and simulation processes was discussed in this paper. There are three techniques which are single stage, balanced, and the feedback was used for wideband power amplifier design. In 1 dB compression point for the simulated amplifier, more than 30 dBm of output power, efficiency (PAE) of 50% and gain of 10 dB are achieved. The design based on feedback topology give the highest gain and output power compared to balanced topology.